PEMANFAATAN SERAT SISAL (agave sisalana L.) DAN LIMBAH PLASTIK PET UNTUK PEMBUATAN BATA RINGAN CLC (CELLULAR LIGHTWEIGHT CONCRETE) - Widyawati, Fauzi (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
Some time ago in the region of West Nusa Tenggara (NTB) experienced earthquake shocks which shocked the community so that many buildings were destroyed and razed to the ground. While the current use of plastic waste is a concern of the community and government, especially in the NTB region. So this background is the basis of research to make earthquake-resistant lightweight bricks by utilizing PET plastic waste to replace coarse aggregate as a mixture and use sisal fiber as a reinforcement to strengthen the strength of lightweight bricks. The purpose of this research is to find out how to make light brick type CLC (Cellular Lightweight Concrete) by utilizing PET plastic waste and sisal fiber, to determine the effect of the addition of PET plastic and sisal fiber to the mechanical properties of light bricks, and to determine the optimum composition of the addition of plastic PET and sisal fiber in the manufacture of lightweight brick CLC. The use of PET plastic and sisal fiber produces brick with an average density of 1,830,419 kg / m3 for 1: 1 variation samples, 1,880 kg / m3 for 4: 1 variation samples, and 1,887,654 kg / m3 for 1: variation samples 4. Maximum compressive strength is achieved in 1: 4 variation samples ie samples with the addition of sisal fiber 4 times more than PET plastic. Based on the results of the measurement of the density of bricks, only the sample variation 1: 1 that meets the standards of SNI 2847-2013 light brick (1,140-1,840 kg / m3). The addition of sisal fiber which is 4 times more than PET plastic (sample variation 1: 4) has the highest compressive strength value of 8.5 MPa and is included in the category of lightweight brick quality I.